Na urdidura das ruínas : o percurso criativo de Douglas 'Machado em Um Corpo Subterrâneo - Vaz, Patrícia Costa (Universidade Federal de São Carlos, 2012)
The research contains the study of the creative process of the documentary Um Corpo Subterrâneo (2007), of the brazilian filmmaker Douglas Machado, with the theorist horizon of the studies of process critique. The link of our analysis is the understanding of the creation as a network in process , (SALLES, 2006, p.19) and, therefore, the research proposes the dive into the creation of the documentary, going beyond the analysis of the final film. We will go through the paths of creation with the genetic dossier of the director (note books, editing script , still, edited versions, interviews, among others), and data from his biography and filmography with value to this study that allows to build hypothesis and establish possible relations between these materials and the work that resulted from these connections. Those connections that define the narrative proposal chosen by the filmmaker, that privileges the construction of the other by the memory of the grief, and that point to the poetic project of the director.
Keywords: Documentário (Cinema); Machado, Douglas Denis Amaral, 1964-; Crítica de processo; Memória; Um Corpo Subterrâneo; Processo de Criação; Luto; Douglas Machado; Um Corpo Subterrâneo; Creation Process; Brazilian Documentary; Grief; LINGUISTICA, LETRAS E ARTES::ARTES::CINEMA